2013
DOI: 10.1186/1741-7015-11-100
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for innate immune pathways in environmentally induced autoimmunity

Abstract: There is substantial evidence that environmental triggers in combination with genetic and stochastic factors play an important role in spontaneous autoimmune disease. Although the specific environmental agents and how they promote autoimmunity remain largely unknown, in part because of diverse etiologies, environmentally induced autoimmune models can provide insights into potential mechanisms. Studies of idiopathic and environmentally induced systemic autoimmunity show that they are mediated by common adaptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 170 publications
(219 reference statements)
0
31
0
1
Order By: Relevance
“…12 The first line of defense is the innate immune response, mediated by neutrophils, monocyte/macrophages, natural killer cells, complement, and cytokines, which is triggered by the binding of pathogen-associated molecular patterns to germline-encoded receptors known as pattern recognition receptors 13,14 that include Toll-like receptors (TLRs) and C-type lectin receptors capable of complement activation through the mannose-binding lectin pathway. 13 The innate immune system acts by identifying pathogen-associated molecular patterns, which include bacterial carbohydrates and peptides, mannose, and lipopolysaccharide.…”
mentioning
confidence: 99%
“…12 The first line of defense is the innate immune response, mediated by neutrophils, monocyte/macrophages, natural killer cells, complement, and cytokines, which is triggered by the binding of pathogen-associated molecular patterns to germline-encoded receptors known as pattern recognition receptors 13,14 that include Toll-like receptors (TLRs) and C-type lectin receptors capable of complement activation through the mannose-binding lectin pathway. 13 The innate immune system acts by identifying pathogen-associated molecular patterns, which include bacterial carbohydrates and peptides, mannose, and lipopolysaccharide.…”
mentioning
confidence: 99%
“…In contrast, type I interferon production does not appear to be involved [50]. The role of altered innate immune cell responses was also noted by Nyland et al [51], who found that prior mercury exposure caused a problematic, macrophage-driven response to viral infection in mice, leading to cardiac inflammation and an increased likelihood of autoimmunity.…”
Section: Mercurymentioning
confidence: 83%
“…Pollard and Kono [50] argue that mercury induces autoimmunity in individuals with a genetic predisposition and that the process involves alterations among innate immune cells that utilize nucleic acid-binding and toll-like receptors and need increased pro-inflammatory cytokine production. In contrast, type I interferon production does not appear to be involved [50].…”
Section: Mercurymentioning
confidence: 99%
“…To this point it is not known how combination of contaminated environment and parasitism can infl uence development of immune response where regulatory (helper lymphocytes, cytokines) and effector (macrophages) components are important in the host defence against parasite. Specifi cally when these immune cells are also target structures for the heavy metals (Šoltys et al, 1997;Valko et al, 2005;Pollard & Kono, 2013). Mice are monogastric animals in which the liver and kidneys serve as detoxifi cation organs that help to eliminate toxic waste metabolites from the body.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of organisms to the heavy metal ions impairs hosts immunocompetence and increases susceptibility to the infections. Heavy metals also affect the cell physiology and modulate immune system responses (Valko et al, 2005;Holmes et al, 2009;Jomova & Valko, 2011;Hemdan et al, 2013;Pollard & Kono, 2013;Dvorožnáková & Jalčová, 2013). Due to high abundance of industrial heavy metals in exposed areas small mammals migrating in affected territories are suitable bioindicators of anthropogenic environmental pollution.…”
Section: Introductionmentioning
confidence: 99%